How computers work a journey into the walk-through computer - Linde, Nancy; Palfreman, John; Educational Video Network; Karol Video (Firm); Computer Museum (Marlborough, Mass.); Chedd-Angier Production Company (Huntsville, TX: Educational Video Network [publisher] ; Wilkes Barre, PA : Karol Video [distributors], 1990)
Heil and a group of teens walk through a huge working-model of a desktop computer learning the functions of random access, chips, video boards, the CPU and other computer parts
Presenter: David Heil
Keywords: Computers